(untitled) (Journal of Health, Population and Nutrition, 2012)
This paper assesses both out-of-pocket payments for healthcare and losses of productivity over six months postpartum among women who gave birth in Matlab, Bangladesh. The hypothesis of the study objective is that obstetric morbidity leads women to seek care at which time out-of-pocket expenditure is incurred. Second, a woman may also take time out from employment or from doing her household chores. This loss of resources places a financial burden on the household that may lead to reduced consumption of usual but less important goods and use of other services depending on the extent to which a household copes up by using savings, taking loans, and selling assets. Women were divided into three groups based on their morbidity patterns: (a) women with a severe obstetric complication (n=92); (b) women with a less-severe obstetric complication (n=127); and (c) women with a normal delivery (n=483). Data were collected from households of these women at two time-pointsat six weeks and six months after delivery. The results showed that maternal morbidity led to a considerable loss of resources up to six weeks postpartum, with the greatest financial burden of cost of healthcare among the poorest households. However, families coped up with loss of resources by taking loans and selling assets, and by the end of six months postpartum, the households had paid back more than 40% of the loans. DOI: http://dx.doi.org/10.3329/jhpn.v30i2.11315 J HEALTH POPUL NUTR 2012 Jun;30(2):205-212